2020
DOI: 10.1364/oe.389133
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving the optical transmission matrix of a multimode fiber using the extended Kalman filter

Abstract: Characterizing the transmission matrix (TM) of a multimode fiber (MMF) benefits many fiber-based applications and allows in-depth studies on the physical properties. For example, by modulating the incident field, the knowledge of the TM allows one to synthesize any optical field at the distill end of the MMF. However, the extraction of optical fields usually requires holographic measurements with interferometry, which complicates the system design and introduces additional noise. In this work, we developed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 49 publications
0
32
0
1
Order By: Relevance
“…Last, the experimental setup with our method is simpler compared to those of holographical methods which usually require optical reference arms that increase the complexity and can degrade the stability of the system. Several algorithms were reported for TM characterization in reference-arm-free setups [ 14 , 24 , 29 , 30 , 45 48 ], however, these works were mainly focused on producing incident wavefronts based on the achieved TM to focus light through fibers or diffusers. The lack of phase information in output speckles made it challenging to retrieve images directly from the measured TM and speckle intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Last, the experimental setup with our method is simpler compared to those of holographical methods which usually require optical reference arms that increase the complexity and can degrade the stability of the system. Several algorithms were reported for TM characterization in reference-arm-free setups [ 14 , 24 , 29 , 30 , 45 48 ], however, these works were mainly focused on producing incident wavefronts based on the achieved TM to focus light through fibers or diffusers. The lack of phase information in output speckles made it challenging to retrieve images directly from the measured TM and speckle intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al proposed a method to calibrate the TM based on the SSM and an iterated extended Kalman filter [52]. Conceptually, they switch the role of the input field and the TM of a conventional SSM.…”
Section: Measuring the Transmission Matrix Of A Multi-mode Fibrementioning
confidence: 99%
“…Secondly, it utilizes the universal statistical property of the speckle phenomenon without a priori information or volumetric data correction. Recent studies have shown that the SSM methods achieve holographic imaging and sensing through turbidity [51,52], which will pave the way for new applications in various spectral domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital optical phase conjugation (DOPC) was also studied for WS with a LC-SLM [ 7 ], in which a laser beam was focused at the target position at one end of a MMF and the conjugated field of the transmitted light at the other end was projected back to focus at the original focusing point. TM-based methods were also studied [ 1 , 3 , 6 , 27 , 28 ], in which the light transport characteristics of a disordered medium was modelled as a complex-valued TM, which was then estimated in a characterisation measurement. Subsequently an optimal input field was determined to correct for the light field changes according to the estimated TM to generate an optical focus.…”
Section: Introductionmentioning
confidence: 99%